Person-Centredness In Human Services: An Evidence-Based Conceptualisation To Inform Practice - Waters, Rebecca Adriana (Curtin University, 2019)
The term ‘person-centred’ is increasingly used in human services to define desirable approaches to service delivery for vulnerable groups of people. This multi-stage, iterative study uses a post-structuralist approach to build a conceptualisation of person-centredness with relevance across the ageing, disability, and mental health sectors. The resultant framework and conceptual model informs the application of person-centredness across policy, organisational and front-line practice contexts.